Porous Hollow Fiber Nickel Electrodes for Effective Supply and Reduction of Carbon Dioxide to Methane through Microbial Electrosynthesis - Alqahtani, Manal F.; Katuri, Krishna P.; Bajracharya, Suman; Yu, Yuanlie; Lai, Zhiping; Saikaly, Pascal Elias (Advanced functional materials, 2018)
Microbial electrochemical reduction of CO2 gas to value‐added chemical products requires the development of an electrode architecture with a three‐phase interface for efficient mass transport. A hybrid bioinorganic system for CO2 reduction to CH4 is developed by coupling a new electrode architecture with enriched methanogenic community. The novel electrode design consists of porous nickel hollow fibers, which act as an inorganic electrocatalyst for hydrogen generation from proton reduction and as a gas‐transfer membrane for direct CO2 delivery to CO2‐fixing hydrogenotrophic methanogens (biological catalyst) on the cathode through the pores of the hollow fibers. These unique features of the electrode create a suitable environment for the enrichment of methanogens, which utilize the hydrogen as a source of reducing equivalents for the conversion of CO2 to CH4. The performance of the nickel electrode is tested in microbial electrosynthesis cells operated at cathode potential of −1 V versus Ag/AgCl, achieving high faradaic efficiency of 77% for CH4. The superior performance of the hybrid bioinorganic system is attributed to the electrode architecture, which provides a three‐phase boundary for gas–liquid reactions, with the reactions supported by the inorganic and biological catalysts. Nickel‐based conductive, catalytic, and porous hollow fiber for effective microbial electrochemical reduction of CO2 to methane; hence addressing two challenges facing society in the current century (i.e., energy crisis and global warming).